modeling an event analysis system for lot - atia, brahim; barika, bachire (universty of elouedجامعة الوادي, 2020)
" أصبحت ثورة إنترنت الأشياء في غضون سنوات قليلة هي مستقبل الفاعلين في تكنولوجيا المعلومات مثل: الشبكة الذكية و التحكم في المنازل والصحة المتصلة والصناعة والخدمات اللوجستية و التسيير الحضري والزراعة. بسبب هذه الثورة ، ستنتج الكائنات المتصلة كتلة كبيرة من البيانات التي يجب رصدها وجمعها وتحليلها لضمان استغلالها وعملها بشكل صحيح وتحسين تجربة المستخدم بشكل استباقي قدر الإمكان. تعد القدرة على تحليل هذه البيانات نقطة تفاضل مهمة لجميع حلول إنترنت الأشياء ،و المناهج الكلاسيكية (الأكثر استخدامًا اليوم هي خوارزميات العتبات ,تنقيب البيانات و خوارزميات توقع مجرى الأمور) التي تهدف إلى معالجة البيانات التقليدية تعاني من إخفاقات. لأن هذه الأدوات لم يتم تطويرها لمواجهة تحديات بيانات إنترنت الأشياء. يعد استخدام التقنيات القائمة على أساليب الذكاء الاصطناعي (مثل: التعلم الآلي والتعلم العميق) تحديًا جديدًا في أنظمة إنترنت الأشياء ، حيث إنه يجعل من الممكن استغلال كميات هائلة من البيانات وينطوي على تطوير قدرة المعالجة باستمرار. كجزء من هذا العمل ، نحقق في اقتراح بنية لأداة تحليل البيانات لـنظام مراقبة منصة إنترنت الأشياء. ستستخدم هذه الأداة طرق الذكاء الاصطناعي لمعالجة البيانات التي تم جمعها بواسطة مستشعرات متصلة وتوفر تنبؤًا ذكيًا بالداث و كشف الشذوذ إذا وجد في تدفقات البيانات. ""In this study, we integrate intelligence technology, the Internet of Things, and distributed systems in a single structure to form a model that incorporates the most important characteristics and advantages of these technologies and produces a product that surpasses the challenges presented by the nature of their work. To achieve this goal, we adopt the Internet of Things as a work ground. And we divide the processor architecture between fog and cloud each for the best work load. For the transfer and processing of data, we use Apache Kafka and Apache Flink for their functionality mode. And finally, we incorporate the artificial intelligence technique to generate the inference model . The work goes through several phases, each including theoretical comparisons that made the option that responds to the largest number of characteristics of our model in its method of operation to be weighted. Except for the last step, as a tracking technique, we make an applied comparison between the different candidate options to decide the appropriate model according to the case being handled. The result,we designed a model that can be adopted to develop a monitoring system that relies on the Internet of things as a source of data and deep learning as a core for analyzing and extracting data directives , within a complex structure of distributed system that allow scalability and availability of service To the fullest extent this is all in the context of fault tolerance.Also we approved by experimental that Multilayer perceptron neural network is the appropriate method for our use case."
mémouer de fin master infourmatique
Keywords: انترنت الاشياء ، كائن متصل، شبكات الاستشعار ، تحليل انترنت الاشياء، تعلم الآلة، التعلم العميق.; internet of things, connected object, Sensor networks, IoT Analytic, Machine Learning.